Transcriptome and Proteome Response of Rhipicephalus annulatus Tick Vector to Babesia bigemina Infection - Antunes, Sandra; Couto, Joana; Ferrolho, Joana; Sanches, Gustavo Seron; Merino Charrez, José Octavio; De la Cruz Hernández, Ned; Mazuz, Monica; Villar, Margarita; Shkap, Varda; de la Fuente, José; Domingos, Ana (Frontiers in Physiology, 2019)
A system biology approach was used to gain insight into tick biology and interactions between vector and pathogen. Rhipicephalus annulatus is one of the main vectors of Babesia bigemina which has a massive impact on animal health. It is vital to obtain more information about this relationship, to better understand tick and pathogen biology, pathogen transmission dynamics and new potential control approaches. In ticks, salivary glands (SGs) play a key role during pathogen infection and transmission. RNA sequencing (RNA-seq) obtained from uninfected and B. bigemina infected SGs obtained from fed female ticks resulted in 6823 and 6475 unigenes, respectively. From these, 360 unigenes were found to be differentially expressed (p < 0.05). Reversed phase liquid chromatography–mass spectrometry (RT-LC-MS/MS) identified a total of 3679 tick proteins. Among them 406 were differently represented in response to Babesia infection. The omics data obtained suggested that Babesia infection lead to a reduction in the levels of mRNA and proteins (n=237 transcripts, n=212 proteins) when compared to uninfected controls. Integrated transcriptomics and proteomics datasets suggested a key role for stress response and apoptosis pathways in response to infection. Thus, six genes coding for GP80, death-associated protein kinase (DAPK-1), bax inhibitor-1 related (BI-1), heat shock protein (HSP), heat shock transcription factor (PHSTF), and queuine trna-ribosyltransferase (QtRibosyl) were selected and RNA interference (RNAi) performed. Gene silencing was obtained for all genes except phstf. Knockdown of gp80, dapk-1 and bi-1 led to a significant increase in Babesia infection levels while hsp and QtRibosyl knockdown resulted in a non-significant decrease of infection levels when compared to the respective controls. Gene knockdown did not affect tick survival, but engorged female weight and egg production were affected in the gp80, dapk-1, and QtRibosyl-silenced groups in comparison to controls. These results advanced our understanding of tick-Babesia molecular interactions, and suggested new tick antigens as putative targets for vaccination to control tick infestations and pathogen infection/transmission.